Otoritas Laki-Laki Dan Perempuan: Studi Penafsiran Kontekstual Abdullah Saeed terhadap Qs. an-Nisa 4: 34 - Shomad, Abdus (STAI Darul Kamal NW Kembang Kerang, 2022)
The superiority of men over women often occurs because of the use of the Qur'anic argument in understanding the position of women in social life, including in their position as leaders. It can be observed and described in verse Qs. an-Nisa' verse 34. The keyword Qawwamuna is often used as an excuse and defense to explain the position of women in Islam. This happens not only in the vocabulary of verses, but also in the role of textual interpretation which forgets the context when this verse was revealed and the contextual conditions of life today. Qs. an-Nisa' verse 34 is often interpreted in contexts that are no longer relevant today. To gain a contextual understanding of